Effect of stimulus sweep direction on distortion product otoacoustic emission fine structure - Marniza Omar; Kapadia S.; Lutman M.E (penerbit ukm, 2004)
The purpose of this study was to examine the effect of stimulus sweep direction on the fine structure of the 2f1-f2 distortion product otoacoustic emission (DPOAE). It was hypothesised that the DPOAE fine structure could be shifted if the stimulus sweep changed from one direction to the other. In the present study, ascending, descending and random frequency sweeps were used, with f2 frequency varying between 992 Hz and 2496 Hz and f2/f1 fixed at 1.22. DPOAE fine structure was recorded at 16 Hz intervals. Screening, spontaneous otoacoustic emission (SOAE) and DPOAE measurements were carried out on 19 ears of 19 subjects aged between 22 and 30 years. Data from 14 ears that had at least one significant peak or valley in their DPOAE fine structure were included in the main analysis. Of these, five ears showed at least one occurrence of SOAE over the frequency span 600 Hz to 2500 Hz. Data for ears with and without SOAEs were grouped and analysed separately. The results showed no effect of sweep direction on DPOAE fine structure. No significant differences were observed in peak or valley frequencies, peak height or valley depth between the three stimulus sweep conditions (p > 0.05). There was also no significant effect of stimulus sweep direction on DPOAE level at the point at which SOAE frequency equalled DPOAE frequency (p > 0.05). In conclusion, the study found no effect of stimulus sweep direction on the fine structure of the 2f1-f2 DPOAE, either in ears with or without SOAEs.Therefore, future measurements of this fine structure may use either sweep direction.